PENGARUH KUALITAS PELAYANAN DENGAN KEPUASAN PENGGUNA JASA TRAILER PT. GUNA LINTAS SARANA SURABAYA - Ladamu, Anhar; Maruta, IGN Anom; Pujianto, Agung (Jurnal Dinamika Administrasi Bisnis, 2016)
This study aims to determine the effect of service quality on customer satisfaction at PT. Cross Means to Surabaya. Respondents were drawn as many as 70 consumer companies. The questionnare measured with Likert scale, then analyzed with multiple linear regression analysis techniques. The result showed that together the independent variable in this study consists of physical from reliability, responsivness, empathy and assurance significantly affects the dependent variable is customer satisfaction due F hitung findings obtained in the numbers 6,985 and supported with a significance level (p)<0,05. Reliability has a number t count of 2,573 with 0,012 significance so that reliability significantly affect customer satisfactionvariable. Responsiveness has number t count of 2.510 with 0,015 significance so that responsiveness significantly affect customer satisfaction variable. Empaty has a number t count of 2,319 with 0,006 significance that empaty significantly affect customer satisfaction variabel. Warranty has a number t count of 2,868 with 0,024 significanse so assurance significantly affect customer satisfaction variable.Â Keyword: Service Quality, Customer Satisfaction.